LABOR CONFLICT WITH ETHNIC CONDITIONS AT THE TENGIZ FIELD OF ATYRAU REGION - Amanzhol Kalysh; Bassanov Zhanzhigit (Research Retrieval and Academic Letters, 2023)
The article deals with the conflict between Kazakh-Turkish workers in the Zhylyoy district of Atyrau region. Since Kazakhstan is a multinational state, the topic of ethnoconflictology is becoming relevant at the moment. In general, similar conflicts are repeated in other regions of the country. Therefore, this is one of the main problems facing our country. We have devoted this publication to the consideration of peaceful ways to solve this problem.